EFEKTIVITAS PIDANA PENJARA DALAM MEMBINA NARAPIDANA - Aryana, I Wayan Putu Sucana (DiH: Jurnal Ilmu Hukum, 2015)
Abstract:Â Imprisonment is the most frequent primary sanction imposed by the judge. It is influenced by classical thinking about retaliation against the perpetrators. Implementation of imprisonment has not been effective to provide coaching and preparing the former inmates to return to society. Prison will only be a place for someone to learn about committing crimes more professional. Negative stigma always attached to ex-prisoners, so they are hard to get back into his social life. One attempt to minimize the imposition of imprisonment is to resolve the criminal matter amicably out of court (through penal mediation). Completion of a criminal case in a peaceful manner will reduce the workload for law enforcement and provide better justice for perpetrators, victims and their families.Keywords: imprisonment, inmates and penal mediation.